VIPoma Crisis: Immediate and life saving reduction of massive stool volumes on starting treatment with octreotide - ElShafie, Omayma (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2011)
We report the case of a 57-year-old male physician who presented with a life threatening secretory and refractory diarrhoea of around 20 L/day. This was complicated by severe hypotension, hypokalaemia, hypercalcaemia, renal failure requiring dialysis, metabolic acidosis, cardiorespiratory arrest and ventilation for 12 days. His diarrhoea responded immediately to the first dose of a therapeutic trial of subcutaneous octreotide 100 mcg 8 hourly which was started on clinical grounds alone before any investigations were carried out. After one day he was extubated and his blood pressure returned to normal. When a functioning neuroendocrine tumour is suspected clinically, the use of octreotide can, as in this case, be life saving.